The Spiritual-Semantic Group of Phrases in the Works of Khudoyberdi Tokhtaboyev - Kizi, Nigora Joranazarova Kurbanboy (International Journal on Integrated Education, 2023)
In this article, the moral-semantic group of phraseologisms in the works of Khudoyberdi Tokhtaboyev was discussed and expressed in percentages. Attention was paid to the writer's use of phraseologisms in their place from a moral-semantic point of view.